1996
DOI: 10.1152/jappl.1996.80.5.1581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lung inflation and airway muscle tone on airway diameter in vivo

Abstract: How normal airway dimensions change with lung volume is of great importance in determining flow limitation during the normal forced vital capacity maneuver as well as in the manifestation of obstructive lung disease. The literature presents a confusing picture, with some results suggesting that airway diameter increases linearly with the cube root of lung volume and others showing a highly nonlinear relation. The effect of smooth muscle contraction on lung-airway interdependence is even less well understood. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
97
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 1 publication
14
97
0
Order By: Relevance
“…Consistent with previous work examining the pressure-area curves in canine airways [4], the relaxed airways were found to be quite distensible at pressures ,10 cmH 2 O and quite rigid above this pressure. Similarly, with airway contraction, this previous work also showed that the airways at low pressures could be quite stiff, only enlarging at the highest pressures.…”
Section: -Week Interval (104¡2% At 3 Weeks and 103¡1% At 5 Weeks)supporting
confidence: 89%
See 4 more Smart Citations
“…Consistent with previous work examining the pressure-area curves in canine airways [4], the relaxed airways were found to be quite distensible at pressures ,10 cmH 2 O and quite rigid above this pressure. Similarly, with airway contraction, this previous work also showed that the airways at low pressures could be quite stiff, only enlarging at the highest pressures.…”
Section: -Week Interval (104¡2% At 3 Weeks and 103¡1% At 5 Weeks)supporting
confidence: 89%
“…Although it is possible that there was still some noncholinergic tone after the large-dose atropine, previous work in the dog model has showed that this is too small to detect with the imaging methods used [4].…”
Section: -Week Interval (104¡2% At 3 Weeks and 103¡1% At 5 Weeks)mentioning
confidence: 98%
See 3 more Smart Citations